Economic and financial sanctions of the United States : legal perspectives / Caf Dowlah, University of Miami Law School. - Dowlah, Caf, 1958- (Cambridge University Press, 2025)
From the Cold War era to the current century, the United States has wielded substantial authority in imposing sanctions. This book delves into the intricate and multifaceted landscape of US economic and financial sanctions, unravelling their historical development, legal foundations, and geopolitical motivations. Case studies on five of the most-sanctioned countries in the world - Russia, Iran, Iraq, Cuba, and Venezuela-provide a deeper understanding of how the sanctioning measures allow the US to extend its reach beyond its national boundaries through extraterritorial laws, sophisticated enforcement mechanisms, and the pervasive dollar-denominated global economic structure. Meticulous and nuanced, this book is a go-to resource for understanding sanction regimes from both multilateral and unilateral perspective and the relevant international laws and jurisprudence.